THE RATE OF HOSPITAL MORBIDITY IN THE ADULT POPULATION WITH MAXILLOFACIAL PATHOLOGY IN THE KRASNODAR REGION - A. N. Redko; A. V. Zobenko; V. Ya. Zobenko; I. T. Rubcova (Кубанский научный медицинский вестник, 2016)
The authors present the results of the study of hospital morbidity of different nosological forms of maxillofacial pathology in the adult population of the Krasnodar region in 2015 in the sex and age distribution. In the structure of pathology inflammatory diseases (65.2%), neoplasms (18.8%) and injuries (15.1%) predominate. Hospital incidence of various forms of maxillofacial pathology in male population was significantly higher than that of women's (331,6 and 212,3 per 100 thousand population respectively). In the age group 18-29 the highest value of this indicator - 338,6 per 100 thousand population - has been determined.